IDENTIFIKASI SERTA HUBUNGAN KONSTRUKSI SUMUR GALI TERHADAP KANDUNGAN COLIFORM PADA AIR SUMUR GALI DI DUSUN JIKEN KABUPATEN LOMBOK TIMUR - Yuliansari, Dini (Bioscientist : Jurnal Ilmiah Biologi, 2019)
The well is one of the source water used for bathing, washing, and drinking by the citizens in Jiken Hamlet, Rarang Village, Terara Sub-District. Poor dug well construction conditions can affect the amount of coliform bacteria contained in the dug well water. The purpose of this study is to identify the construction of dug wells and the content of coliform bacteria in dug well water and determine the relationship between dug well construction and the content of coliform bacteria. This research is analytic with a cross sectional study design. The results were obtained from 11 samples of dug wells which were observed in construction and the coliform content was known that all samples did not requirements as good dug well construction. Coliform content test results showed that as many as 5 dug well water samples did not pass the clean water quality standards. The results of data analysis with the chi-square test variable construction of dug wells with coliform content variableÂ showed 0,172 > 0,05, then the concluded is the dug well not suitable to use by people in that area as a source of water for daily needs.